Implementation of Performance Measurement Systems at PT. Pos Indonesian - Muhamad Jupri; Hamka Hamka; Ruly Budiono (International Journal of Business, Economics, and Social Development, 2020)
This paper aims to carry out performance measurement at PT. Pos Indonesia, which consists of measurements of financial and non-financial performance. The preparation of this paper uses the study method of various literature from various international article sources. Public sector organizations or institutions in implementing their financial and non-financial performance measurements use a variety of steps. Therefore, the managers of PT. Pos Indonesia must adjust the appropriate performance measurement system, such as what will be used by PT. Pos Indonesia, according to the conditions of each PT. Pos Indonesian.